Development of a Skyglow Investigation System for Simulated Urban Environment - Srinivasan, Yuvaneshwaran; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2026)
The emergence of Artificial Light at Night (ALAN) has generated an urban skyglow that is disturbing astronomy performances as well as the local biomes. Pricey satellite data or fancy photometers are usually used for Skyglow detection, although these systems do not capture the actual effects of city shapes and lighting configurations of the glow on a small scale. The purpose of this project was to bridge that gap by constructing a low cost, small-scale skyglow investigation system capable of simulating and quantifying light pollution in a regulated, urban-like environment. To capture readings of light illuminance, the TSL2591 High Dynamic Range Digital Light Sensor and paired with a smartphone fisheye lens as a visual support was used. The experiment consisted of multiple variables which include testing the linearity of the system with brightness levels ranging between 0 to 10, vertical attenuation between 0 to 25 cm, spatial spread with a grid scan and shielding efficiency by comparing an unshielded and shielded system. The findings indicated that there is a definite linear association between the source brightness and the skyglow and the vertical data demonstrated the existence of an Urban Canyon effect where in the reflections slow the attenuation forecast. We might even observe a spatial Light Dome in the unshielded form reaching its maximum zenith light with 1.48 Lux which was reduced by Full Cut-Off shielding to a meager 0.07 Lux at 95.27 % reduction. These results confirm that our prototype is a robust instructional and exploration tool on studying the mechanics of skyglow and as an example of how geometric shielding is an essential engineering resource to address the problem of light pollution in cities.